Men of Valor : Tangled Webs : Book 3 - Hannon, Irene (Grand Rapids, Michigan : Revell, a division of Baker Publishing Group, 2016)
"After a disastrous Middle East mission ends his six-year Army Ranger career, Finn McGregor needs some downtime. A peaceful month in the woods sounds like the perfect way to decompress. But peace isn't on the agenda once he crosses paths with publishing executive Dana Lewis, a neighbor who is nursing wounds of her own. Someone seems bent on disrupting her stay in the lakeside cabin she inherited from her grandfather"--Amazon.com.
Keywords: Veterans -- Fiction; Publishers and publishing -- Fiction; Man-woman relationships -- Fiction; Vacation homes -- Fiction; Christian fiction; Detective and mystery fiction